2016
DOI: 10.1523/jneurosci.3395-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

How the Human Brain Represents Perceived Dangerousness or “Predacity” of Animals

Abstract: Common or folk knowledge about animals is dominated by three dimensions: (1) level of cognitive complexity or "animacy;" (2) dangerousness or "predacity;" and (3) size. We investigated the neural basis of the perceived dangerousness or aggressiveness of animals, which we refer to more generally as "perception of threat." Using functional magnetic resonance imaging (fMRI), we analyzed neural activity evoked by viewing images of animal categories that spanned the dissociable semantic dimensions of threat and tax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 56 publications
3
43
0
Order By: Relevance
“…Additionally, within the ventral stream, more anterior informational networks more strongly reflect the learned categorical structure for both groups of participants. This anterior-to-posterior hierarchy is consistent with previous findings that highlight the increased conceptual and categorical knowledge represented in more anterior regions of the ventral visual stream (Connolly et al, 2016;Connolly & Haxby, 2012;Rugg & Thompson-Schill, 2013). Lastly, the observed dorsalto-ventral shift also echoes the concrete-to-abstract conceptual change described in the developmental learning literature (Bruner, 1973;Bruner, 1966;Fyfe, McNeil, Son, & Goldstone, 2014).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Additionally, within the ventral stream, more anterior informational networks more strongly reflect the learned categorical structure for both groups of participants. This anterior-to-posterior hierarchy is consistent with previous findings that highlight the increased conceptual and categorical knowledge represented in more anterior regions of the ventral visual stream (Connolly et al, 2016;Connolly & Haxby, 2012;Rugg & Thompson-Schill, 2013). Lastly, the observed dorsalto-ventral shift also echoes the concrete-to-abstract conceptual change described in the developmental learning literature (Bruner, 1973;Bruner, 1966;Fyfe, McNeil, Son, & Goldstone, 2014).…”
Section: Discussionsupporting
confidence: 90%
“…1B). Fitting the expert model of mechanical similarity into a DSM allows for a robust comparison of expert and novice representational spaces, across behavioral and neural responses and between mechanical and naïve models of similarity (Connolly et al, 2016;Kriegeskorte, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several investigations have pointed to a possible relationship between ToM and threat perception. Connolly et al (2016), for example, showed that when evaluating the dangerousness or predaticity of various animals the human brain relies on an area called the superior temporal sulcus. As pointed out in the introduction, this area is centrally implicated in the control of both face recognition and mindreading.…”
Section: Eye Contact and Threatmentioning
confidence: 99%